2019
DOI: 10.1111/spol.12500
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the delivery of cash‐for‐care payments across Europe

Abstract: The article aims to understand how governments across Europe have modified the regulation of the delivery of cash‐for‐care schemes (CfCs) to dependent older people since the beginning of the century. In our terminology, the regulation of the CfCs delivery defines the norms, rules, and practices that public actors adopt to manage how beneficiaries can use the benefits. To discuss the regulation of CfCs delivery, we employ an original framework that take three analytical dimensions into account: the degrees of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…In contrast, the French care plan is designed by a professional team. In the Netherlands, users need to present documentary evidence of expenditures (Gori & Luppi, 2019).…”
Section: Cfc: Not So Similarmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the French care plan is designed by a professional team. In the Netherlands, users need to present documentary evidence of expenditures (Gori & Luppi, 2019).…”
Section: Cfc: Not So Similarmentioning
confidence: 99%
“…Recently, cash transfers have been introduced as tools in the LTCSs of high-income countries. Cash transfers, or cash-for-care (CfC), are an alternative (usually cheaper) to the direct (in-kind) provision of services (Gori & Luppi, 2019). According to international evidence, this plan may widen the coverage, control the cost, and broaden the choices of beneficiaries and encourage the commodification of the care market (Gori & Morciano, 2019; Le Bihan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Their numerical application suggested that a de-risking strategy based on disability derivatives can be a viable solution to reduce the portfolio riskiness of long-term care insurers. Gori and Luppi [ 15 ] investigated how governments in six countries across Europe have regulated the delivery of cash-for-care schemes to dependent older people. By taking into account three analytical dimensions -- cash-for-care utilization dimension, professional support dimension, and the relationship between the delivery of cash-for-care and the delivery of the other publicly funded long-term care inputs—they showed that there has been a shared and increased interest in consolidating the regulation of cash-for-care delivery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empirical evidence has demonstrated that CDC contributes to better care outcomes for older adults, including health status and quality of life (Carlson et al, 2007;Fleming et al, 2019). Policy design is crucial to shaping consumer direction, which can eventually produce positive outcomes for older adults since policies determine the extent to which flexibility, support mechanisms, and service types are available to consumers (Gori & Luppi, 2019). However, existing studies have depicted sporadic aspects of CDC policies, including policy objectives, cost containment strategies, regulations on quality assurance, care worker wages and fringe benefits, and ways by which consumers direct service delivery (Colombo et al, 2011;Da Roit & Le Bihan, 2010;Lundsgaard, 2005;Wiener et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, existing studies have depicted sporadic aspects of CDC policies, including policy objectives, cost containment strategies, regulations on quality assurance, care worker wages and fringe benefits, and ways by which consumers direct service delivery (Colombo et al, 2011;Da Roit & Le Bihan, 2010;Lundsgaard, 2005;Wiener et al, 2003). Current literature lacks discussion and comparative evidence on how CDC policy designs facilitate consumer direction through a holistic and cross-national comparative approach (Gori & Luppi, 2019;Gross et al, 2015). A comparative framework to examine the metrics in the CDC components could facilitate understanding current CDC implementations and describe unique or similar policy features operated in each country, which could further strengthen the future CDC policy development.…”
Section: Introductionmentioning
confidence: 99%